PENGEMBANGAN DESAIN MODEL PEMBELAJARAN BLENDED LEARNING PADA METODE NUMERIK: BLENDED COOPERATIVE LEARNING - Siti Aminah (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2020)
This study aims to develop design of blended learning model, and then call Blended Cooperative Learning model (BCL). This research is research development. Stages of the research use Thiagarajan, Semmel and Semmel development model. this study limited by 3 stages. There are the define stage, the design stage,  and the developing stage. This research was attended at STIKI Malang in Informatics Engineering students taking Numerical Method courses. Data collection techniques used validation sheets for the design of BCL Model and materials to two validators. Data analysis uses average scoring. The results of this study are design of BCL model and materials. The materials are materials learning in LMS, RPP, and worksheets. The results of this study is design of blended learning Blended Cooperative Learning is feasible to use.